The Effect of Workload, Job Satisfaction, and Work Motivation on Turnover Intention at PT. Rohul Sawit Industri Ujung Batu - Putri Mala Sari Lubis; Kurniawaty Fitri; Ahmad Rifqi (Westscience Press, 2026)
This study aims to analyze the effect of Workload, Job Satisfaction, and Work Motivation on turnover intention at PT. Rohul Sawit Industri Ujung Batu. This study uses a quantitative approach with a questionnaire distribution method. The population in this study were employees of PT. Rohul Sawit Industri Ujung Batu, with a sampling technique using probability sampling. Data were analyzed using multiple linear regression tests with the help of SPSS 25. These results indicate that workload has a positive and significant effect on intention to quit. Furthermore, job satisfaction and work motivation have a negative and partially significant effect on intention to quit. Simultaneously, workload, job satisfaction, and work motivation all have a significant effect on turnover intention.